2019
DOI: 10.1371/journal.pone.0221921
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal antibiotics exposure and the risk of autism spectrum disorders: A population-based cohort study

Abstract: Background Prenatal antibiotic exposure induces changes in infants’ gut microbiota composition and is suggested as a possible contributor in the development of autism spectrum disorders (ASD). In this study, we examined the association between prenatal antibiotic exposure and the risk of ASD. Methods This was a population-based cohort study utilizing the Manitoba Population Research Data Repository. The cohort included 214 834 children born in Manitoba, Canada between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 29 publications
(22 reference statements)
3
45
1
Order By: Relevance
“…Our results indicated that pre- and postnatal antibiotic use increased the ASD risk. This is consistent with previous reports that pre- and postnatal antibiotic use causes ASD in children [10,13,17,18,19]. In our study, both pre- and postnatal antibiotic use increased the ASD risk (Figure 2); however, only prenatal, but not postnatal, antibiotic use was significantly elevated in children with ASD compared to controls (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results indicated that pre- and postnatal antibiotic use increased the ASD risk. This is consistent with previous reports that pre- and postnatal antibiotic use causes ASD in children [10,13,17,18,19]. In our study, both pre- and postnatal antibiotic use increased the ASD risk (Figure 2); however, only prenatal, but not postnatal, antibiotic use was significantly elevated in children with ASD compared to controls (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, infant mercury poisoning caused by seafood consumption by the mother, pediatric vaccination, and prenatal use of antibiotics has been suggested to cause ASD [9]. Moreover, studies have reported that pre- [10,11,12] and postnatal exposure to antibiotics and acetaminophen increases the ASD risk [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple factors could contribute in dysbiosis in ASD, including the restricted diets that they follow, in response to allergies and gastrointestinal discomfort [39]. As the gut microbiota expands greatly after birth, several investigators explored the possibility of the role of early exposure to antibiotics, either prenatally or at early life, in causing this dysbiosis [100,101]. Indeed, oral antibiotics disrupt the gut microbiota by indirectly promoting the growth of pathogenic microbiota resulting in GIS [100].…”
Section: The Altered Microbiota Of People With Autismmentioning
confidence: 99%
“…Prenatal antibiotic use is also associated with increased risk of childhood asthma [15] and obesity [16]. Although other conditions have been associated with early life antibiotic exposure, some of the data is conflicting such as with autism spectrum disorder (ASD) [17], while other emerging evidence suggests that neonatal antibiotic use increases the risk of developing functional gastrointestinal disorders including infantile colic and regurgitation [18]. Given that antibiotic use during pregnancy and/or intrapartum will continue to be clinically indicated, it is crucial to identify ways in which the risks of this early life antibiotic exposure, particularly on the developing brain and behavior, can be mitigated.…”
Section: Introductionmentioning
confidence: 99%